Happily Ever After? A Critical Examination of the Gothic in Disney Fairy Tale Films - Rutherford, Amanda (Auckland University of Technology, 2021)
This thesis critically examines four Disney fairy tale films across the 20th and 21st centuries to assess the changes in the representation of Gothic tone and intent. I have taken a qualitative approach and deployed a close textual analysis of the films, finding that there are four main themes: magic and the supernatural; monsters and villains; body modification and identity; and the gendered, patriarchal systems. The films that comprise my sample are Sleeping Beauty (1959), Beauty and the Beast (1991), Maleficent (2014), and Beauty and the Beast (2017), and span a period of almost sixty years in Disney film-making history. Although there are four films in my sample, there are only two stories and these stories are established and well-known. The Disney versions are comparable to both the earliest forms and later literary forms of the fairy stories. Disney fairy films have entertained audiences for decades, and on the surface the stories appear to be innocuous entertainment, but something has changed. The later version of these films continue to appear benign, yet on close inspection, contain a substantial growth in the volume, tone and intent of the dark, horrific aspects of Gothic narrative. By considering the socio-political and cultural context of the times when these films were produced, I discuss the differences that can be found within the films: the messages that the films individually and collectively present; and how the Disney films have been utilised to promote the company’s conservative worldview. I have found there is a marked increase in the Gothic representation in three of the four themes I isolated. There are fewer differences in the treatment of gender and patriarchy than there are in the other themes. At times the films of the 21st century appear to be transgressive, but the rhetoric and tropes presented ultimately remain the same, with constant representation of patriarchal systems of power over women; the stereotypical heterosexual relationship between male and female dominating all other relationships; where love conquers all (if you are white and heterosexual); and that good, (a nebulous ideal) will always prevail over evil. In concluding, the Gothic mode serves to assess the cultural anxieties and normative messages that the Disney fairy tale films contain, and show that the Disney films of the 21st century represent an ever-darkening, increasingly tangled world of Gothic horror and gender stereotypes.
Keywords: Disney; Gothic; Body modification; Gender; Supernatural; Monsters; Villains; Patriarchy; Sleeping Beauty; Beauty and the Beast; Maleficent; Political economy